2021
DOI: 10.3390/biomedicines9081043
|View full text |Cite
|
Sign up to set email alerts
|

Poloxamer 188 Exerts Direct Protective Effects on Mouse Brain Microvascular Endothelial Cells in an In Vitro Traumatic Brain Injury Model

Abstract: Traumatic Brain Injury (TBI), the main contributor to morbidity and mortality worldwide, can disrupt the cell membrane integrity of the vascular endothelial system, endangering blood–brain barrier function and threatening cellular subsistence. Protection of the vascular endothelial system might enhance clinical outcomes after TBI. Poloxamer 188 (P188) has been shown to improve neuronal function after ischemia/reperfusion (I/R) injury as well as after TBI. We aimed to establish an in vitro compression-type TBI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 72 publications
1
10
0
Order By: Relevance
“…This includes the lowest cell viability and the worst membrane leakage, indicated by LDH release and FM1-43 incorporation, which makes reperfusion the critical turning point to intervene pharmacologically. Similar to a previous study in mouse brain microvascular ECs [36], our data indicate that P188 treatment upon reperfusion produced a dose-dependent attenuation of membrane leakage and cell death in mouse coronary artery ECs.…”
Section: Protection By P188supporting
confidence: 90%
“…This includes the lowest cell viability and the worst membrane leakage, indicated by LDH release and FM1-43 incorporation, which makes reperfusion the critical turning point to intervene pharmacologically. Similar to a previous study in mouse brain microvascular ECs [36], our data indicate that P188 treatment upon reperfusion produced a dose-dependent attenuation of membrane leakage and cell death in mouse coronary artery ECs.…”
Section: Protection By P188supporting
confidence: 90%
“…Theoretically, the expression of CD31 in the NCHA group was expected to surpass that of the Gel group, yet experimental results revealed the contrary. Through a comprehensive review of the literature, it was found that high-molecular weight hyaluronic acid might hinder vascular formation [ 45 , 46 ], whereas F68 demonstrated a protective effect on damaged microvascular endothelial cells [ 47 ], which could elucidate this phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…Endothelial cells are integral to the function of the blood-brain barrier, and their detachment and disruption alters the function of the tight junctions in the blood-brain barrier which increases the permeability of injurious substances. Lotze et al investigated the effect of P188 on mouse brain microvascular endothelial cells in a combined model of simulated IR and compression (TBI) [ 16 , 56 ]. Mild injury models underwent 1 h of compression at the start of a 5-h hypoxia/2-h reoxygenation exposure.…”
Section: Astrocyte Endothelial Cell and Neuronal In Vitro Models Of T...mentioning
confidence: 99%